Sediment Thickness Estimation in Serpong Experimental Power Reactor Site Using HVSR Method - Theo Alvin Ryanto; Eko Rudi Iswanto; Yuni Indrawati; Abimanyu BW Setiaji; Hadi Suntoko (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2020)
A study about sediment thickness mapping was conducted in Serpong Experimental Power Reactor Site. This reactor is planned to be built in a high seismic activity area. Sediment thickness is one of many factors that could affect the site response. A high sediment deposit could amplify and prolong the earthquake waves. This condition could make the reactor building more vulnerable to seismic hazard. The sediment thickness was estimated using the microtremor HVSR method. The parameter used for sediment thickness calculation was obtained from the borehole and cross-hole seismic survey and was tested to ensure that the chosen parameter and the method were accurate. The deviation found in the borehole data was also calculated to determine the accuracy level of the calculation. The current planned location for the reactor is in a relatively low sediment deposit area with 8.8 m of thickness, however there is an area, west of the current location that might be a better location for the reactor based on the result of this study.